2021
DOI: 10.21203/rs.3.rs-801232/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validating an Amharic Version of the 36-item Short Form Health Survey (SF-36) in Individuals With Leprosy in Ethiopia.

Abstract: Background: Health-related quality of life (HRQoL) has now become an indispensable outcome measure in many randomized clinical trials and other studies. It provides the patient’s voice in measuring health improvement or decline and assessing treatment effectiveness. A validated Amharic version of HRQoL assessment tool was needed for leprosy clinical trials in Ethiopia. The SF-36 was chosen but a validated Amharic version was not available. We describe how this was developed.Methods: The SF-36 was translated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The SF-36 questionnaire is the gold standard for assessing HRQoL. The SF-36 has been administered to various populations across different cultural settings in over 60 languages and more than 7,000 studies, including in SSA ( Wyss et al., 1999 ; Patel et al., 2017 ; Kuo and Operario, 2011 ; Verduin et al., 2014 ; Lambert et al., 2021 ). Reliability studies of the SF-36 in SSA have demonstrated high internal consistency (Cronbach's alpha >0.80) ( Wyss et al., 1999 ; Patel et al., 2017 ; Kuo and Operario, 2011 ; Verduin et al., 2014 ; Lambert et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SF-36 questionnaire is the gold standard for assessing HRQoL. The SF-36 has been administered to various populations across different cultural settings in over 60 languages and more than 7,000 studies, including in SSA ( Wyss et al., 1999 ; Patel et al., 2017 ; Kuo and Operario, 2011 ; Verduin et al., 2014 ; Lambert et al., 2021 ). Reliability studies of the SF-36 in SSA have demonstrated high internal consistency (Cronbach's alpha >0.80) ( Wyss et al., 1999 ; Patel et al., 2017 ; Kuo and Operario, 2011 ; Verduin et al., 2014 ; Lambert et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The SF-36 has been administered to various populations across different cultural settings in over 60 languages and more than 7,000 studies, including in SSA ( Wyss et al., 1999 ; Patel et al., 2017 ; Kuo and Operario, 2011 ; Verduin et al., 2014 ; Lambert et al., 2021 ). Reliability studies of the SF-36 in SSA have demonstrated high internal consistency (Cronbach's alpha >0.80) ( Wyss et al., 1999 ; Patel et al., 2017 ; Kuo and Operario, 2011 ; Verduin et al., 2014 ; Lambert et al., 2021 ). The SF-36 is separated into eight domains: general health perception, physical functioning, role-physical functioning, bodily pain, vitality, social functioning, role-emotional functioning and mental health.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was selected by reviewing relevant literatures on the subject to ensure reliability (23,24). The Amharic version of the SF-36 questioner was used (25). Training was conducted for data collectors on the purpose of study, procedures of data collection for one day prior to the study.…”
Section: Data Quality Assurancementioning
confidence: 99%